Time-lapse imaging of molecular evolution by high-throughput sequencing. Issue 15 (3rd July 2018) - Nguyen Quang, Nam; Bouvier, Clément; Henriques, Adrien; Lelandais, Benoit; Ducongé, Frédéric
Abstract: High-throughput sequencing of in vitro selection could artificially provide large quantities of relic sequences from known times of molecular evolution. Here, we demonstrate how it can be used to reconstruct an empirical genealogical evolutionary (EGE) tree of an aptamer family. In contrast to classical phylogenetic trees, this tree-diagram represents proliferation and extinction of sequences within a population during rounds of selection. Such information, which corresponds to their evolutionary fitness, is used to infer which sequences may have been mutated through the selection process that led to the appearance and spreading of new sequences. This approach was validated by the re-analysis of an in vitro selection that had previously identified an aptamer against Annexin A2. It revealed that this aptamer might be the descendant of a sequence that was more highly amplified in early rounds. It also succeeded in predicting improved variants of this aptamer and providing a means to understand the influence of selection pressure on evolution. This is the first demonstration that HTS can provide time-lapse imaging of the evolutionary pathway that is taken by a macromolecule during in vitro selection to evolve by successive mutations through better fitness.